REAKSI MASYARAKAT TERHADAP PEMBUANGAN LIMBAH PABRIK SAWIT DI SUNGAI LONGE (STUDI KASUS DI PT. SURYA AGROLIKA REKSA PMKS KOTO BARU) - M. Prisandi; Askarial (SISI LAIN REALITA, 2022)
Waste is waste generated from an industrial process whose presence in a place is not desired by the environment because of its destructive nature. Disposal of waste can be in the form of gas, solid and liquid waste. Disposal in the form of liquid waste can cause environmental pollution, it can happens when the the waste does not meet the quality of the waste. Disposal of waste can damage and pollute the surrounding environment. Moreover, it will be very detrimental when the environment is something that used daily by community. It also can cause an unfavorable reaction from the community. The purpose of this study was to determine the reaction of the community to the disposal of palm oil mill waste in the longe river at PT. Surya Agrolika Koto Baru PMKS. The method used in this study is a qualitative method with a descriptive approach. The theory used in this research is conflict theory. The results of this study explain that the community's reaction caused by the disposal of palm oil mill waste PT Surya Agrolika Reksa PMKS Koto Baru is that there are protests by the community to the PT due to the disposal of factory waste. However, the action ended peacefully with the community being asked to sign a letter, which turned out to be detrimental to the community itself.